When to Use Methadone for pain: A Case-Based Approach - Palat, Gayatri (Indian J Palliat Care, 2018)
The case studies are written in this article to illustrate how methadone might be used for pain in the Indian context. These cases might be used for discussion in a multidisciplinary team, or for individual study. It is important to understand that pain requires a multidisciplinary approach as opioids will assist only with physical, i.e. neuropathic and nociceptive pain, but not emotional, spiritual, or relational pain or the pain of immobility. The social determinants of pain were included to demonstrate how emotional, relational, and psychological dimensions of pain amplify the physical aspects of pain. The case studies follow a practical step-wise approach to pain while undergoing cancer treatment, pain toward the end-of-life and needing longer acting opioid. Methadone in children, and methadone in conditions of opioid toxicity or where there is a need for absorption in the proximal intestine cases are included.